Spontaneous S-Si bonding of alkanethiols to Si(111)-H: Towards Si-molecule-Si circuits - Peiris, Chandramalika; Ciampi, Simone; Dief, Essam; Zhang, Jinyang; Canfield, P.J.; Le Brun, A.P.; Kosov, D.S.; Reimers, J.R.; Darwish, Nadim (ROYAL SOC CHEMISTRY, 2020)
We report the synthesis of covalently linked self-assembled monolayers (SAMs) on silicon surfaces, using mild conditions, in a way that is compatible with silicon-electronics fabrication technologies. In molecular electronics, SAMs of functional molecules tethered to goldviasulfur linkages dominate, but these devices are not robust in design and not amenable to scalable manufacture. Whereas covalent bonding to silicon has long been recognized as an attractive alternative, only formation processes involving high temperature and/or pressure, strong chemicals, or irradiation are known. To make molecular devices on silicon under mild conditions with properties reminiscent of Au-S ones, we exploit the susceptibility of thiols to oxidation by dissolved O2, initiating free-radical polymerization mechanisms without causing oxidative damage to the surface. Without thiols present, dissolved O2would normally oxidize the silicon and hence reaction conditions such as these have been strenuously avoided in the past. The surface coverage on Si(111)-H is measured to be very high, 75% of a full monolayer, with density-functional theory calculations used to profile spontaneous reaction mechanisms. The impact of the Si-S chemistry in single-molecule electronics is demonstrated using STM-junction approaches by forming Si-hexanedithiol-Si junctions. Si-S contacts result in single-molecule wires that are mechanically stable, with an average lifetime at room temperature of 2.7 s, which is five folds higher than that reported for conventional molecular junctions formed between gold electrodes. The enhanced “ON” lifetime of this single-molecule circuit enables previously inaccessible electrical measurements on single molecules.